2023
DOI: 10.1051/0004-6361/202142205
|View full text |Cite
|
Sign up to set email alerts
|

Planetary evolution with atmospheric photoevaporation

Abstract: Context. Observations by the Kepler satellite have revealed a gap between larger sub-Neptunes and smaller super-Earths that atmospheric escape models had predicted as an evaporation valley prior to discovery. Aims. We seek to contrast results from a simple X-ray and extreme-ultraviolet (XUV)-driven energy-limited escape model against those from a direct hydrodynamic model. The latter calculates the thermospheric temperature structure self-consistently, including cooling effects such as thermal conduction. Besi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 110 publications
0
3
0
Order By: Relevance
“…The planetary mass-loss rate Ṁp depends on the stellar XUV flux at the orbital distance of the exoplanet, which we compute according to the host star's spectral type from Lammer, H. et al (2009). The precise XUV flux at a system is a subject of ongoing theoretical work on photoevaporation on a population of exoplanets (Affolter, L. et al, 2023;Mordasini, 2020). According to this calculation the exomoons orbit inside the Alfvén spheres even for heating efficiencies up to 30%, such that the plasma is driven into a rigid corotation with the planet at a ☽ < R mag similar to the case of Io in the Solar System (see Table 3).…”
Section: Magnetosphere and Plasma Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The planetary mass-loss rate Ṁp depends on the stellar XUV flux at the orbital distance of the exoplanet, which we compute according to the host star's spectral type from Lammer, H. et al (2009). The precise XUV flux at a system is a subject of ongoing theoretical work on photoevaporation on a population of exoplanets (Affolter, L. et al, 2023;Mordasini, 2020). According to this calculation the exomoons orbit inside the Alfvén spheres even for heating efficiencies up to 30%, such that the plasma is driven into a rigid corotation with the planet at a ☽ < R mag similar to the case of Io in the Solar System (see Table 3).…”
Section: Magnetosphere and Plasma Environmentmentioning
confidence: 99%
“…(2009). The precise XUV flux at a system is a subject of ongoing theoretical work on photoevaporation on a population of exoplanets (Affolter, L. et al., 2023; Mordasini, 2020). According to this calculation the exomoons orbit inside the Alfvén spheres even for heating efficiencies up to 30%, such that the plasma is driven into a rigid corotation with the planet at a<Rmag ${a}_{{\rightmoon}}< {R}_{\text{mag}}$ similar to the case of Io in the Solar System (see Table 3).…”
Section: Candidate Systemsmentioning
confidence: 99%
“…Along with core-powered mass loss (Ginzburg et al 2018;Gupta & Schlichting 2019), photoionization-driven atmospheric escape is thought to play a significant role in shaping the observed properties of the Kepler planet population (Fulton et al 2017), likely contributing to carving the observed radius valley by stripping sub-Neptune-sized planets of their primordial envelopes and turning them into rocky cores (e.g., Owen & Wu 2013Rogers & Owen 2021;Affolter et al 2023;Owen & Schlichting 2024).…”
Section: Introductionmentioning
confidence: 99%